EU update. Issue 1 (February 2017) - Burden, Kit
Abstract: This is the latest edition of the DLA Piper column on developments in EU law relating to IP, IT and telecommunications. This news article summarises recent developments that are considered important for practitioners, students and academics in a wide range of information technology, e-commerce, telecommunications and intellectual property areas. It cannot be exhaustive but intends to address the important points. This is a hard copy reference guide, but links to outside web sites are included where possible. No responsibility is assumed for the accuracy of information contained in these links.